Biosorptive Removal of Cr(VI) from Aqueous Solution by Araucaria Cunninghamii Linn: A Multivariate Study. (24th May 2021) - Dilshad, Asma; Anwer, Humera; Shah, Faheem; Siddiqui, Asma; Muhammad, Haji; Ali, Nida; Hanif, Muddasir; Mahmood, Talat
Abstract: Hexavalent chromium (Cr(VI)) is carcinogenic, mutagenic, teratogenic and affects liver, lungs, kidney and nervous system by oxidizing DNA and proteins. Therefore, leaves of Araucaria cunninghamii Linn (AC) were used as a low cost biosorbent to remove Cr(VI) from aqueous solution. To achieve this goal, the optimal conditions for Cr(VI) biosorption were established for pH (2), temperature (323 K), biosorbate (25 ppm) and biosorbent (1.4 g/L) concentrations, mesh size (74 to 149 µm) and stirring time (60 min). Plackett-Burman experimental design was applied which supported the obtained results except biosorbent particle size and Cr(VI) concentration. Central composite design (CCD) showed a second order polynomial model which was established by a higher Fischer's F statistical value and the percentage biosorptive removal for Cr(VI) to be 99%. Thermodynamic parameters were also applied to validate the assay which showed that the process is endothermic (+ΔH°) and spontaneous (−ΔG°) in nature. The biosorbent-biosorbate bond was shown to have a chemisorptive nature. Moreover, the observed reaction followed the dynamics of pseudo second order kinetics. The Langmuir and Freundlich adsorption isotherms results indicated that biosorption of Cr(VI) was homogenous and multilayered and the adsorption capability was determined to be 9.1644 mg/g at 323 K. The Fourier transform infrared (FTIR) spectra of loaded and unloaded Araucaria cunninghamii Linn confirmed the presence of N–H, C–O and C–X functional groups in biosorption process. Furthermore, energy dispersive x-ray spectroscopy (EDS) analysis confirmed the presence of Cr(VI) ions in the loaded biomass. The irregularities on the surface of the scanning electron microscopic (SEM) images validated these results.